Pathology, Risk Factors, and Oxidative Damage Related to Type 2 Diabetes-Mediated Alzheimer's Disease and the Rescuing Effects of the Potent Antioxidant Anthocyanin. (27th February 2021) - Khan, Muhammad Sohail; Ikram, Muhammad; Park, Tae Ju; Kim, Myeong Ok
Abstract : The pathology and neurodegeneration in type 2 diabetes- (T2D-) mediated Alzheimer's disease (AD) have been reported in several studies. Despite the lack of information regarding the basic underlying mechanisms involved in the development of T2D-mediated AD, some common features of the two conditions have been reported, such as brain atrophy, reduced cerebral glucose metabolism, and insulin resistance. T2D phenotypes such as glucose dyshomeostasis, insulin resistance, impaired insulin signaling, and systemic inflammatory cytokines have been shown to be involved in the progression of AD pathology by increasing amyloid-beta accumulation, tau hyperphosphorylation, and overall neuroinflammation. Similarly, oxidative stress, mitochondrial dysfunction, and the generation of advanced glycation end products (AGEs) and their receptor (RAGE) as a result of chronic hyperglycemia may serve as critical links between diabetes and AD. The natural dietary polyflavonoid anthocyanin enhances insulin sensitivity, attenuates insulin resistance at the level of the target tissues, inhibits free fatty acid oxidation, and abrogates the release of peripheral inflammatory cytokines in obese (prediabetic) individuals, which are responsible for insulin resistance, systemic hyperglycemia, systemic inflammation, brain metabolism dyshomeostasis, amyloid-beta accumulation, and neuroinflammatory responses. In this review, we have shown that obesity may induce T2D-mediated AD and assessed the recent therapeutic advances, especially the use of anthocyanin, against T2D-mediated AD pathology. Taken together, the findings of current studies may help elucidate a new approach for the prevention and treatment of T2D-mediated AD by using the polyflavonoid anthocyanin.